ANALISIS DAYA SAING USAHATANI BUAH NAGA DI KECAMATAN INSANA (Studi Kasus Desa Nunmafo) - Anunut, Jefrianto; Joka, Umbu; Kune, Simon Juan; Taena, Werenfidus; Sipayung, Boanerges Putra (Agriprimatech, 2024)
Dragon fruit plants are one of the plants that have very high economic value, dragon fruit plants are also very helpful in improving the economy both at the regional and national levels. The purpose of this study was to determine; 1) the benefits of dragon fruit farming in Nunmafo Village; and 2) the competitiveness of dragon fruit farming in Nunmafo Village. The analysis method used in this study is the PAM (Policy Analysis Matrix) analysis method. The results of the study showed that; 1) Dragon fruit farming in Nunmafo Village has a profit where the private profit is 34,072,000 and the social profit is 13,447,000 and 2) Dragon fruit farming in Nunmafo Village has competitiveness because the RBP (Private Cost Ratio) value is 0.47 and the RBSP (Domestic Resource Cost Ratio) is 0.69. Government policy can be seen in the PAM (Policy Analysis Matrix) analysis ratio, namely the nominal input protection coefficient (KPIN) of 0.65, the nominal output protection coefficient (KPON) of 1.25, the effective protection coefficient (KPN) of 1.47, the profit coefficient (KK) of 2.53, and the producer subsidy ratio (RSP) of 0.34.